Early-phase administration of human amnion-derived stem cells ameliorates neurobehavioral deficits of intracerebral hemorrhage by suppressing local inflammation and apoptosis - Kuramoto, Yoji; Fujita, Mitsugu; Takagi, Toshinori; Takeda, Yuki; Doe, Nobutaka; Yamahara, Kenichi; Yoshimura, Shinichi (Journal of neuroinflammation, 2022)
Background Intracerebral hemorrhage (ICH) is a significant cause of death and disabilities. Recently, cell therapies using mesenchymal stem cells have been shown to improve ICH-induced neurobehavioral deficits. Based on these findings, we designed this study to evaluate the therapeutic efficacy and underlying mechanisms by which human amnion-derived stem cells (hAMSCs) would ameliorate neurobehavioral deficits of ICH-bearing hosts. Methods hAMSCs were induced from amnia obtained by cesarean section and administered intravenously to ICH-bearing mice during the acute phase. The mice were then subject to multitask neurobehavioral tests at the subacute phase. We attempted to optimize the dosage and timing of the hAMSC administrations. In parallel with the hAMSCs, a tenfold higher dose of human adipose-derived stem cells (ADSCs) were used as an experimental control. Specimens were obtained from the ICH lesions to conduct immunostaining, flow cytometry, and Western blotting to elucidate the underlying mechanisms of the hAMSC treatment. Results The intravenous administration of hAMSCs to the ICH-bearing mice effectively improved their neurobehavioral deficits, particularly when the treatment was initiated at Day 1 after the ICH induction. Of note, the hAMSCs promoted clinical efficacy equivalent to or better than that of hADSCs at 1/10 the cell number. The systemically administered hAMSCs were found in the ICH lesions along with the local accumulation of macrophages/microglia. In detail, the hAMSC treatment decreased the number of CD11b + CD45 + and Ly6G + cells in the ICH lesions, while splenocytes were not affected. Moreover, the hAMSC treatment decreased the number of apoptotic cells in the ICH lesions. These results were associated with suppression of the protein expression levels of macrophage-related factors iNOS and TNFα. Conclusions Intravenous hAMSC administration during the acute phase would improve ICH-induced neurobehavioral disorders. The underlying mechanism was suggested to be the suppression of subacute inflammation and apoptosis by suppressing macrophage/microglia cell numbers and macrophage functions (such as TNFα and iNOS). From a clinical point of view, hAMSC-based treatment may be a novel strategy for the treatment of ICH.